EFEKTIFITAS MODEL PEMBEJARAN KOOPERATIF TIPE TGT DALAM MENINGKATKAN KETERAMPILAN SOSIAL PESERTA DIDIK DI UPTD SMPN 1 BANGKALAN - Novita Trisanti; Rinie Pratiwi; Yulita Fitriyah (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Education is one of the important things for a developing country like Indonesia, therefore Indonesia continues to innovate to improve the quality of existing education, one of which is by implementing an independent curriculum taking into account Indonesia's diverse cultural background. One of the principles of independence is a safe and comfortable learning atmosphere. To create this atmosphere, good social skills are needed. Therefore, the aim of this research is to determine the effectiveness of cooperative learning with TGT type on students' social skills. This research is a classroom action research that uses 2 cycles with the Kemmis and Mctaggart model, which consists of 4 steps, planning, action, observation and reflection. The results of this research are that the TGT type cooperative learning model can improve students' scientific literacy skills based on 5 aspects of scientific literacy indicators, namely relationships with peers, self-control, academic ability, obedience and self-assertiveness.